2012
DOI: 10.1021/bm300015s
|View full text |Cite
|
Sign up to set email alerts
|

Synthetically Simple, Highly Resilient Hydrogels

Abstract: Highly resilient synthetic hydrogels were synthesized by using the efficient thiol-norbornene chemistry to cross-link hydrophilic poly(ethylene glycol) (PEG) and hydrophobic polydimethylsiloxane (PDMS) polymer chains. The swelling and mechanical properties of the hydrogels were well-controlled by the relative amounts of PEG and PDMS. In addition, the mechanical energy storage efficiency (resilience) was more than 97% at strains up to 300%. This is comparable with one of the most resilient materials known: natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(149 citation statements)
references
References 42 publications
2
147
0
Order By: Relevance
“…56,57,58 PEG and PS were chosen as model co-network components for several reasons. Many studies on PS-PEG block copolymers have been reported, and their phase behavior is well known.…”
Section: Resultsmentioning
confidence: 99%
“…56,57,58 PEG and PS were chosen as model co-network components for several reasons. Many studies on PS-PEG block copolymers have been reported, and their phase behavior is well known.…”
Section: Resultsmentioning
confidence: 99%
“…We further implement the delayed dissipation and resilient domain by pre-stretching interpenetrating-network hydrogels to damage the short-chain network within controlled ranges, achieving extremely high resilience (~95%) and high toughness (~1900 J/m 2 ) (see Fig. 5 for comparison with counterpart biological and synthetic hydrogels [1,2,4,12]). Since the design principle and method reported here are material-independent, we expect they can be used to make existing tough hydrogels resilient and to design future tough and resilient hydrogels.…”
Section: Experimental Validation and Results -mentioning
confidence: 99%
“…Designing synthetic hydrogels that are both tough and resilient will not only help the replacement and regeneration of relevant tissues such as heart valves, but also advance fundamental knowledge in mechanics and materials science. Despite the successes in developing hydrogels with high toughness [5][6][7][8][9][10][11] or high resilience [12,13], recent efforts on designing both tough and resilient hydrogels mostly focus on one property (e.g. reporting resilience without toughness) [14][15][16].…”
mentioning
confidence: 99%
“…These properties are a function of the material itself, as well as bioprinting process parameters ( Figure 1B). Printed tensile specimens have been used to investigate the interaction of lines and layers [9][10][11][12][13][14][15][16][17], however, a systematic investigation of how process parameters influence these properties has not been conducted. Terminology to describe the tensile measurements include two crucial aspects.…”
Section: Introductionmentioning
confidence: 99%